Increasing proficiency in information management and information resources : the modern information professional : final survey report - Mullings, Blossom (UWI. Dept. of Library Studies KingstonJM, 1995)
Focuses on the competencies, responsibilities, affiliations and job context of the information professional, with the objective of arriving at a definition of tasks and functions of the modern information professional. Seeks to determine guidelines for organization development of the Department of Library Studies, University of the West Indies with emphasis on programme development and orientation.